2019
DOI: 10.35862/2688-7487/64/10
|View full text |Cite
|
Sign up to set email alerts
|

Journal of Pregnancy and Newborncare

Abstract: Perinatal morbidity is defined as presence of the disease which occurs as a result of side effect influences of treatment acting either on a fetus during pregnancy or newborn during the first week of life Young, [1]. The perinatal morbidity rates continue to increase despite the advancing maternal and neonatal care services in the Capricorn district, Limpopo province. Its prevention has major medical, social and economic costs. In the developing countries, the risk of perinatal morbidity is six times greater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Another study confirmed that student midwives were seen as a division of workforce, as they were expected to manage pregnant women without supervision. [6,14] In this regard, students absented themselves, as they did not want to be used as part of the workforce in the units. [6] It is imperative that every unit should be provided with clinical learning outcomes so that the learning needs of students are always taken into consideration.…”
Section: Come Delivery Time You Have To Run To the Sluice Room To Cle...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study confirmed that student midwives were seen as a division of workforce, as they were expected to manage pregnant women without supervision. [6,14] In this regard, students absented themselves, as they did not want to be used as part of the workforce in the units. [6] It is imperative that every unit should be provided with clinical learning outcomes so that the learning needs of students are always taken into consideration.…”
Section: Come Delivery Time You Have To Run To the Sluice Room To Cle...mentioning
confidence: 99%
“…A shortage of clinical teaching resources has been highlighted, in particular in rural settings in SA. [14,23] In these situations, only partial teaching and learning took place, which resulted in challenges regarding completion of the midwifery register.…”
Section: • Limited Experiential Learning Due To Covid-19mentioning
confidence: 99%